A solar cell and a photovoltaic module
By adding a fluorescent nano-passivation antireflection film to the surface of solar cells, long-wavelength light is converted into visible light, solving the optical loss problem of crystalline silicon solar cells and improving photoelectric conversion efficiency and stability.
Patent Information
- Application Number
- CN202310166459.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-13
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-02-13
AI Technical Summary
Existing solar cells suffer from optical loss, which limits photoelectric conversion efficiency and stability. This is mainly due to the high reflectivity and low light absorption coefficient of crystalline silicon, as well as the blocking of incident light by the front metal grid lines.
A fluorescent nano-passivation antireflection film, including polyvinyl chloride, o-nitrophenyl octyl ether, aminated silica microspheres, and fluorescent nanopowder, is added to the surface of solar cells. The fluorescent nanomaterials convert long-wavelength light into visible light, thereby increasing the energy spectrum absorption range.
It reduces optical losses, improves optical utilization and photoelectric conversion efficiency, and enhances the stability of solar cells.
Smart Images

Figure CN116130526B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of solar cells, and more specifically, to a solar cell and a photovoltaic module. Background Technology
[0002] Currently, photovoltaic power generation is recognized as one of the effective ways to solve energy crises and environmental pollution. However, the optical losses inherent in solar cells affect their photoelectric conversion efficiency and stability. First, the main raw material for solar cell production is crystalline silicon. Crystalline silicon has a refractive index of around 3.8, while air has a refractive index slightly greater than 1, a significant difference. When sunlight shines on the surface of crystalline silicon, this difference in refractive index causes a large portion (30%-40%) of the incident light to be reflected. Second, crystalline silicon is an indirect bandgap semiconductor material with a relatively low light absorption coefficient. Long-wavelength light incident on the silicon wafer cannot be fully absorbed, causing some light to escape from the back of the cell. Third, the metal grid lines on the front of the crystalline silicon solar cell can block incident light, all of which contribute to the optical losses of the cell.
[0003] Therefore, there is an urgent need to provide a solar cell and photovoltaic module that can reduce optical losses in solar cells. Summary of the Invention
[0004] In view of this, the present invention provides a solar cell comprising a fluorescent nano-passivation antireflection film, wherein the fluorescent nano-passivation antireflection film comprises: 0.1-0.3g polyvinyl chloride, 0.4-0.6g o-nitrophenyl octyl ether, 0.15-0.25g aminated silica microspheres, and 0.05-0.15g fluorescent nanopowder; wherein the fluorescent nanopowder is anti-Stokes fluorescent nanopowder, and the material is: NaYF4:Ln 3+ ; The solar cell further includes a silicon substrate, an emitter, a first passivation layer, a second passivation layer, and a first electrode that penetrates the emitter, the first passivation layer, and the second passivation layer and forms an electrical connection with the silicon substrate, all disposed sequentially on a first surface of the silicon substrate in a direction away from the silicon substrate; and a second electrode that forms an electrical connection with the silicon substrate, disposed on a second surface of the silicon substrate in a direction away from the silicon substrate, wherein the second passivation layer is the fluorescent nano-passivation antireflection film.
[0005] Optionally, the preparation method of the fluorescent nano-passivated antireflective film includes the following steps: Mix 0.1-0.3g of polyvinyl chloride, 0.4-0.6g of o-nitrophenyl octyl ether, 0.15-0.25g of aminated silica microspheres and 0.05-0.15g of fluorescent nanoparticles, and add 1-5 mL of tetrahydrofuran to obtain a mixture; The mixture was homogenized in an ultrasonic apparatus to obtain a suspension; A passivation and antireflection film is deposited on the surface of a solar cell using a suspension coating method.
[0006] Optionally, the fluorescent nanopowder is an anti-Stokes fluorescent nanopowder.
[0007] Optionally, the preparation process of the anti-Stokes fluorescent nanopowder is as follows: a complexing agent and sodium fluoride are added to a lanthanum salt solution to obtain a mixed solution, wherein the concentration of the lanthanum salt solution in the mixed solution is 0.1-2 mol / L, the concentration of the complexing agent is 0.1-2 mol / L, and the concentration of the sodium fluoride is 0.1-1 mol / L.
[0008] Optionally, the lanthanum salt solution is yttrium oxide dissolved in dilute acid, or ytterbium oxide, thulium oxide, or erbium oxide dissolved in dilute acid.
[0009] Optionally, the dilute acid is dilute nitric acid or dilute hydrochloric acid.
[0010] Optionally, the complexing agent is trisodium citrate or disodium EDTA.
[0011] Optionally, the preparation process of the aminated silica microspheres is as follows: Slowly add 2-6 mL of ammonia and 2-6 mL of tetraethyl orthosilicate to 50-100 mL of ethanol and 5-30 mL of distilled water, stir at 20-40°C for 16-32 hours, collect the fixed product, and obtain silicon dioxide. Add 1-4 g of silicon dioxide After sonicating with 20-80 mL of toluene for 10-30 minutes, slowly add 2-6 mL of 3-aminopropyltriethoxysilane. Under nitrogen protection, stir at 100-150 °C for 10-16 hours. After separating the solid, wash with ethanol and acetone, and vacuum dry at 40-80 °C for 16-32 hours to obtain aminated silica microspheres.
[0012] The present invention provides a photovoltaic module, comprising, from top to bottom, a glass layer, a first encapsulant layer, a solar cell, a second encapsulant layer and a backsheet, wherein the solar cell is any of the aforementioned solar cells.
[0013] Compared with the prior art, the solar cell and photovoltaic module provided by the present invention achieve at least the following beneficial effects: A solar cell includes a fluorescent nano-passivation antireflective film, comprising: 0.1-0.3 g of polyvinyl chloride, 0.4-0.6 g of o-nitrophenyl octyl ether, 0.15-0.25 g of aminated silica microspheres, and 0.05-0.15 g of fluorescent nanoparticles. By adding the fluorescent nano-passivation antireflective film to the surface of the solar cell, the fluorescent nanomaterials convert long-wavelength light into visible light, increasing the energy spectrum absorption range, thereby reducing optical loss and improving optical utilization.
[0014] Of course, any product implementing this invention does not necessarily need to achieve all of the technical effects described above at the same time.
[0015] Other features and advantages of the invention will become clear from the following detailed description of exemplary embodiments of the invention with reference to the accompanying drawings. Attached Figure Description
[0016] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments of the invention and, together with their description, serve to explain the principles of the invention.
[0017] Figure 1 This is a schematic diagram of a solar cell provided by the present invention; Figure 2 This is a flowchart of a method for fabricating a fluorescent nano-passivation antireflection film in a solar cell provided by the present invention; Figure 3 This is another flowchart of the method for fabricating the fluorescent nano-passivation antireflection film in the solar cell provided by the present invention; Figure 4 This is a schematic diagram of a photovoltaic module provided by the present invention; 1-Silicon substrate, 2-Emitter, 3-First passivation layer, 4-Second passivation layer, 5-First electrode, 6-Tunneling oxide layer, 7-Phosphorus-doped polycrystalline silicon layer, 8-Third passivation layer, 9-Second electrode Detailed Implementation
[0018] Various exemplary embodiments of the present invention will now be described in detail with reference to the accompanying drawings. It should be noted that, unless otherwise specifically stated, the relative arrangement, numerical expressions, and values of the components and steps set forth in these embodiments do not limit the scope of the invention.
[0019] The following description of at least one exemplary embodiment is merely illustrative and is in no way intended to limit the invention or its application or use.
[0020] Techniques, methods, and equipment known to those skilled in the art may not be discussed in detail, but where appropriate, such techniques, methods, and equipment should be considered part of the specification.
[0021] In all the examples shown and discussed herein, any specific values should be interpreted as merely exemplary and not as limitations. Therefore, other examples of exemplary embodiments may have different values.
[0022] It should be noted that similar labels and letters in the following figures indicate similar items; therefore, once an item is defined in one figure, it does not need to be discussed further in subsequent figures.
[0023] Reference Figure 1 The present invention provides a solar cell 100, comprising a fluorescent nano-passivation antireflection film, the fluorescent nano-passivation antireflection film comprising: 0.1-0.3g polyvinyl chloride, 0.4-0.6g o-nitrophenyl octyl ether, 0.15-0.25g aminated silica microspheres and 0.05-0.15g fluorescent nanopowder.
[0024] Optionally, the fluorescent nano-passivated antireflective film comprises: 0.1 g polyvinyl chloride, 0.4 g o-nitrophenyl octyl ether, 0.15 g aminated silica microspheres and 0.05 g fluorescent nanopowder.
[0025] Optionally, the fluorescent nano-passivated antireflective film comprises: 0.1 g polyvinyl chloride, 0.4 g o-nitrophenyl octyl ether, 0.2 g aminated silica microspheres and 0.05 g fluorescent nanopowder.
[0026] Optionally, the fluorescent nano-passivated antireflective film comprises: 0.2 g polyvinyl chloride, 0.5 g o-nitrophenyl octyl ether, 0.15 g aminated silica microspheres and 0.05 g fluorescent nanopowder.
[0027] Optionally, the fluorescent nano-passivated antireflective film comprises: 0.2 g polyvinyl chloride, 0.5 g o-nitrophenyl octyl ether, 0.2 g aminated silica microspheres and 0.1 g fluorescent nanopowder.
[0028] Optionally, the fluorescent nano-passivated antireflective film comprises: 0.2 g polyvinyl chloride, 0.5 g o-nitrophenyl octyl ether, 0.2 g aminated silica microspheres and 0.1 g fluorescent nanopowder.
[0029] Optionally, the fluorescent nano-passivated antireflective film comprises: 0.3g polyvinyl chloride, 0.6g o-nitrophenyl octyl ether, 0.25g aminated silica microspheres and 0.15g fluorescent nanopowder.
[0030] Optionally, the fluorescent nano-passivated antireflective film comprises: 0.3g polyvinyl chloride, 0.6g o-nitrophenyl octyl ether, 0.2g aminated silica microspheres and 0.15g fluorescent nanopowder.
[0031] Optionally, the fluorescent nano-passivated antireflective film comprises: 0.3g polyvinyl chloride, 0.6g o-nitrophenyl octyl ether, 0.25g aminated silica microspheres and 0.15g fluorescent nanopowder.
[0032] The fluorescent nano-passivation antireflection film provided in this embodiment is a square sheet film with a thickness of 0.5-30 μm and a side length of 10-30 mm; polyvinyl chloride (PVC) is used as the film matrix, and o-nitrophenyl octyl ether (NPOE) is used as a plasticizer to increase the flexibility of the film; the fluorescent nanopowder is anti-Stokes fluorescent nanopowder, and the material is: NaYF4:Ln 3+ It can convert long-wavelength light into visible light, increasing the energy spectrum absorption range; tetrahydrofuran (THF) is an important organic synthesis raw material and a high-performance solvent, especially suitable for dissolving PVC. After THF evaporates, it forms a PVC film.
[0033] By adding a fluorescent nano-passivation antireflection film to the surface of solar cell 100, the fluorescent nanomaterial converts long-wavelength light into visible light, increasing the energy spectrum absorption range, thereby reducing optical loss and improving optical utilization.
[0034] In some alternative embodiments, reference continues to be made to... Figure 1 The solar cell 100 also includes a silicon substrate 1, an emitter 2, a first passivation layer 3, a second passivation layer 4, and a first electrode 5 that penetrates the emitter 2, the first passivation layer 3, and the second passivation layer 4 and forms an electrical connection with the silicon substrate 1, located on the first surface of the silicon substrate 1 and arranged in a direction away from the silicon substrate 1; a second electrode 9 that is located on the second surface of the silicon substrate 1 and forms an electrical connection with the silicon substrate 1, located in a direction away from the silicon substrate 1; and the second passivation layer 4 is a fluorescent nano-passivation antireflection film.
[0035] It should be noted that the second surface of the silicon substrate 1, located in the direction away from the silicon substrate, may further include a tunneling oxide layer 6, a phosphorus-doped polysilicon layer 7, and a third passivation layer 8 sequentially disposed therefrom. The second electrode penetrates the tunneling oxide layer 6, the phosphorus-doped polysilicon layer 7, and the third passivation layer 8 to form an electrical connection with the silicon substrate. The first passivation layer 3 and the third passivation layer 8 may be silicon nitride layers. Silicon nitride (SiN) x The thin film has excellent surface passivation and anti-reflection properties.
[0036] In some alternative embodiments, refer to Figure 2 The method for fabricating a fluorescent nano-passivated antireflective film includes the following steps: S1 is a mixture of 0.1-0.3g polyvinyl chloride, 0.4-0.6g o-nitrophenyl octyl ether, 0.15-0.25g aminated silica microspheres and 0.05-0.15g fluorescent nanoparticles, and 1-5 mL tetrahydrofuran is added to obtain a mixture. S2 homogenizes the mixture in an ultrasonic instrument to obtain a suspension; S3 uses a suspension coating method to deposit a passivation and antireflection film on the surface of a solar cell.
[0037] Optionally, a mixture of 0.1 g polyvinyl chloride, 0.4 g o-nitrophenyl octyl ether, 0.15 g aminated silica microspheres and 0.05 g fluorescent nanoparticles is prepared by adding 1 mL tetrahydrofuran.
[0038] Optionally, a mixture of 0.1 g polyvinyl chloride, 0.4 g o-nitrophenyl octyl ether, 0.2 g aminated silica microspheres and 0.05 g fluorescent nanoparticles is prepared and 2 mL tetrahydrofuran is added to obtain a mixture.
[0039] Optionally, a mixture of 0.2 g polyvinyl chloride, 0.5 g o-nitrophenyl octyl ether, 0.15 g aminated silica microspheres and 0.05 g fluorescent nanoparticles is prepared by adding 2 mL tetrahydrofuran.
[0040] Optionally, a mixture of 0.2 g polyvinyl chloride, 0.5 g o-nitrophenyl octyl ether, 0.2 g aminated silica microspheres and 0.1 g fluorescent nanoparticles is prepared and 4 mL tetrahydrofuran is added to obtain a mixture.
[0041] Optionally, a mixture of 0.3 g polyvinyl chloride, 0.6 g o-nitrophenyl octyl ether, 0.25 g aminated silica microspheres and 0.15 g fluorescent nanoparticles is prepared and 3 mL tetrahydrofuran is added to obtain a mixture.
[0042] Optionally, a mixture of 0.3 g polyvinyl chloride, 0.6 g o-nitrophenyl octyl ether, 0.2 g aminated silica microspheres and 0.15 g fluorescent nanoparticles is prepared and 4 mL tetrahydrofuran is added to obtain a mixture.
[0043] Optionally, a mixture of 0.3 g polyvinyl chloride, 0.6 g o-nitrophenyl octyl ether, 0.25 g aminated silica microspheres and 0.15 g fluorescent nanoparticles is prepared and 5 mL tetrahydrofuran is added to obtain a mixture.
[0044] The method for fabricating the fluorescent nano-passivated antireflective film provided in this embodiment produces a square sheet film with a thickness of 0.5-30 μm and a side length of 10-30 mm. To meet the practical needs of preparing antireflective films of different thicknesses and sizes, the added polyvinyl chloride, o-nitrophenyl octyl ether, aminated silica microspheres, and fluorescent nanopowder can be increased or decreased proportionally in actual production. Polyvinyl chloride (PVC) is used as the film matrix, and o-nitrophenyl octyl ether (NPOE) is used as a plasticizer to increase the flexibility of the film. The fluorescent nanopowder is anti-X fluorescent nanopowder, and the material is: NaYF4:Ln 3+It can convert long-wavelength light into visible light, increasing the energy spectrum absorption range; tetrahydrofuran (THF) is an organic solvent that evaporates to form a PVC film. Specifically, fluorescent nano-passivated antireflective films can also be prepared by metal-organic chemical vapor deposition.
[0045] By adding a fluorescent nano-passivation antireflection film to the surface of solar cells, fluorescent nanomaterials can convert long-wavelength light into visible light, increasing the energy spectrum absorption range, thereby reducing optical loss and improving optical utilization.
[0046] In some optional embodiments, the fluorescent nanopowder is an anti-Stokes fluorescent nanopowder.
[0047] It should be noted that the anti-Stokes fluorescent nanopowder is prepared by ion copolymerization, hydrothermal method, microwave radiation method, sol-gel method, high-temperature solid phase method, coprecipitation method, combustion method or microemulsion method.
[0048] As is understandable, anti-Stokes materials, also known as upconversion fluorescent materials, are materials that emit short-wavelength light when excited by long-wavelength light. By adding anti-Stokes materials to the surface of solar cells to convert infrared light into visible light, the absorption spectrum of solar cells can be effectively broadened, optical losses reduced, and solar cell efficiency improved.
[0049] In some alternative embodiments, refer to Figure 3 The preparation process of anti-Stokes fluorescent nanopowder is as follows: a complexing agent and sodium fluoride are added to a lanthanum salt solution to obtain a mixed solution, wherein the concentration of the lanthanum salt solution in the mixed solution is 0.1-2 mol / L, the concentration of the complexing agent is 0.1-2 mol / L, and the concentration of sodium fluoride is 0.1-1 mol / L.
[0050] Specifically, the concentration of the lanthanum salt solution can be 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L, 1.6 mol / L, 1.7 mol / L, 1.8 mol / L, 1.9 mol / L, or 2 mol / L; the concentration of the complexing agent can be 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, 1.1 mol / L, or 2 mol / L. The concentrations of sodium fluoride can be 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, or 1 mol / L. As is understandable, anti-Stokes materials, also known as upconversion fluorescent materials, are materials that emit short-wavelength light when excited by long-wavelength light. By adding anti-Stokes materials to the surface of solar cells to convert infrared light into visible light, the absorption spectrum of solar cells can be effectively broadened, optical losses reduced, and solar cell efficiency improved.
[0051] In some alternative embodiments, the lanthanum salt solution is yttrium oxide dissolved in dilute acid, and ytterbium oxide, thulium oxide or erbium oxide dissolved in dilute acid.
[0052] It should be noted that lanthanide metal oxides (Ln2O3) are sparingly soluble in water and alkalis, but readily soluble in acids. A lanthanum salt solution can be obtained by dissolving yttrium oxide in dilute acid, or by dissolving ytterbium oxide, thulium oxide, or erbium oxide in dilute acid.
[0053] In some alternative embodiments, the dilute acid is dilute nitric acid or dilute hydrochloric acid.
[0054] It should be noted that lanthanide metal oxides are poorly soluble in water and alkali. When yttrium oxide is dissolved in dilute acid, and ytterbium oxide, thulium oxide, or erbium oxide is dissolved in dilute nitric acid or dilute hydrochloric acid, the resulting nitrates and chlorides are readily soluble in water.
[0055] In some optional embodiments, the complexing agent is trisodium citrate or disodium EDTA.
[0056] It should be noted that in order to improve the solubility of Ln2O3, a solubilizing agent, namely a complexing agent, needs to be added: trisodium citrate or disodium ethylenediaminetetraacetate. The complexing agent can improve solubility because it forms a structure that coordinates with the metal ion of the metal salt being dissolved, changing the structure of the metal salt molecule from a simple salt to a complex salt. The molecule becomes larger, and its behavior on the electrode also changes, making the sparingly soluble metal salt dissolve well in the aqueous solution.
[0057] In some alternative embodiments, reference continues to be made to... Figure 3 The preparation process of aminated silica microspheres is as follows: Slowly add 2-6 mL of ammonia and 2-6 mL of tetraethyl orthosilicate to 50-100 mL of ethanol and 5-30 mL of distilled water, stir at 20-40°C for 16-32 hours, collect the fixed product, and obtain silicon dioxide. Add 1-4 g of silicon dioxide After sonicating with 20-80 mL of toluene for 10-30 minutes, slowly add 2-6 mL of 3-aminopropyltriethoxysilane. Under nitrogen protection, stir at 100-150 °C for 10-16 hours. After separating the solid, wash with ethanol and acetone, and vacuum dry at 40-80 °C for 16-32 hours to obtain aminated silica microspheres.
[0058] Optionally, the preparation process of aminated silica microspheres is as follows: 2 mL of ammonia and 2 mL of tetraethyl orthosilicate are slowly added dropwise to 50 mL of ethanol and 5 mL of distilled water, stirred at 20°C for 16 hours, and the fixed product is collected to obtain silica; 1 g of silica... After sonicating with 20 mL of toluene for 10 minutes, 2 mL of 3-aminopropyltriethoxysilane was slowly added dropwise. The mixture was stirred at 100 °C for 10 hours under nitrogen protection. The solid was separated, washed with ethanol and acetone, and then vacuum dried at 40 °C for 16 hours to obtain aminated silica microspheres.
[0059] Optionally, the preparation process of aminated silica microspheres is as follows: 3 mL of ammonia and 3 mL of tetraethyl orthosilicate are slowly added dropwise to 60 mL of ethanol and 15 mL of distilled water, stirred at 30°C for 24 hours, and the fixed product is collected to obtain silica; 2 g of silica... After sonicating with 40 mL of toluene for 20 minutes, 3 mL of 3-aminopropyltriethoxysilane was slowly added dropwise. The mixture was stirred at 110 °C for 12 hours under nitrogen protection. The solid was separated, washed with ethanol and acetone, and dried under vacuum at 50 °C for 24 hours to obtain aminated silica microspheres.
[0060] Optionally, 3.5 mL of ammonia and 4 mL of tetraethyl orthosilicate are slowly added dropwise to 70 mL of ethanol and 10 mL of distilled water, stirred at 25°C for 24 hours, and the fixed product is collected to obtain silica. 2 g of silicon dioxide After sonicating with 50 mL of toluene for 20 minutes, 4 mL of 3-aminopropyltriethoxysilane was slowly added dropwise. The mixture was stirred at 110 °C for 12 hours under nitrogen protection. The solid was separated, washed with ethanol and acetone, and then vacuum dried at 50 °C for 24 hours to obtain aminated silica microspheres.
[0061] Optionally, the preparation process of aminated silica microspheres is as follows: 4 mL of ammonia and 4 mL of tetraethyl orthosilicate are slowly added dropwise to 70 mL of ethanol and 20 mL of distilled water, stirred at 40°C for 32 hours, and the fixed product is collected to obtain silica; 3 g of silica... After sonicating with 60 mL of toluene for 25 minutes, 4 mL of 3-aminopropyltriethoxysilane was slowly added dropwise. The mixture was stirred at 130 °C for 16 hours under nitrogen protection. The solid was separated, washed with ethanol and acetone, and then vacuum dried at 60 °C for 32 hours to obtain aminated silica microspheres.
[0062] Optionally, the preparation process of aminated silica microspheres is as follows: 5 mL of ammonia and 5 mL of tetraethyl orthosilicate are slowly added dropwise to 80 mL of ethanol and 25 mL of distilled water, stirred at 35°C for 18 hours, and the fixed product is collected to obtain silica; 4 g of silica... After sonicating with 80 mL of toluene for 30 minutes, 5 mL of 3-aminopropyltriethoxysilane was slowly added dropwise. The mixture was stirred at 140 °C for 16 hours under nitrogen protection. The solid was separated, washed with ethanol and acetone, and then vacuum dried at 70 °C for 28 hours to obtain aminated silica microspheres.
[0063] Optionally, the preparation process of aminated silica microspheres is as follows: 5.5 mL of ammonia and 5 mL of tetraethyl orthosilicate are slowly added dropwise to 90 mL of ethanol and 28 mL of distilled water, stirred at 38°C for 30 hours, and the fixed product is collected to obtain silica; 3 g of silica... After sonicating with 75 mL of toluene for 28 minutes, 5 mL of 3-aminopropyltriethoxysilane was slowly added dropwise. Under nitrogen protection, the mixture was stirred at 145 °C for 14 hours. The solid was separated, washed with ethanol and acetone, and then vacuum dried at 75 °C for 24 hours to obtain aminated silica microspheres.
[0064] Optionally, the preparation process of aminated silica microspheres is as follows: 6 mL of ammonia and 6 mL of tetraethyl orthosilicate are slowly added dropwise to 100 mL of ethanol and 30 mL of distilled water, stirred at 40°C for 32 hours, and the fixed product is collected to obtain silica; 4 g of silica... After sonicating with 80 mL of toluene for 30 minutes, 6 mL of 3-aminopropyltriethoxysilane was slowly added dropwise. The mixture was stirred at 150 °C for 16 hours under nitrogen protection. The solid was separated, washed with ethanol and acetone, and then vacuum dried at 80 °C for 32 hours to obtain aminated silica microspheres.
[0065] Specifically, ammonia water (NH3·H2O) is a 25% ammonia solution, tetraethyl orthosilicate (TEOS) has a concentration of 28-40%, and ethanol is anhydrous ethanol. Ethanol is a co-solvent for water and silicate esters, and an appropriate amount of ethanol can promote the stable reaction.
[0066] It should be noted that silicon is a semiconductor material, and the power generation principle of solar cells mainly utilizes the photoelectric effect of this semiconductor. Silicon has a high refractive index, meaning that light hitting its surface is not fully absorbed; a large portion is reflected. To minimize reflection loss, one or more anti-reflection coatings with matching refractive index and thickness can be deposited on the cell to improve conversion efficiency and increase light transmittance. Passivation anti-reflection coatings prepared using aminated silica microspheres (SiO2-NH2) not only improve cell conversion efficiency but also enhance the crack resistance of the substrate.
[0067] Reference Figure 4 The present invention provides a photovoltaic module, comprising, from top to bottom, a glass layer 10, a first encapsulant layer 11, a solar cell 100, a second encapsulant layer 12, and a backsheet 13.
[0068] Specifically, the first adhesive layer 11 and the second adhesive layer 12 can be any one of ethylene-vinyl acetate copolymer (EVA), ethylene-octene copolymer (POE), or polyvinyl butyral (PVB); the backing plate 13 can be any one of glass, thermoplastic elastomer (TPE), ceramic-plastic polymer composite (CPC), polyvinyl chloride plastic (KPC), polyvinylidene fluoride composite film (KPK), or polyvinyl fluoride composite film (TPT). The photovoltaic module provided in this embodiment includes a solar cell 100. By adding a fluorescent nano-passivation antireflection film to the surface of the solar cell 100, the fluorescent nanomaterial converts long-wavelength light into visible light, increases the energy spectrum absorption range, reduces optical loss, and improves optical utilization, thereby improving the photoelectric conversion efficiency of the photovoltaic module.
[0069] As can be seen from the above embodiments, the solar cell and photovoltaic module provided by the present invention achieve at least the following beneficial effects: A solar cell includes a fluorescent nano-passivation antireflective film, comprising: 0.1-0.3 g of polyvinyl chloride, 0.4-0.6 g of o-nitrophenyl octyl ether, 0.15-0.25 g of aminated silica microspheres, and 0.05-0.15 g of fluorescent nanoparticles. By adding the fluorescent nano-passivation antireflective film to the surface of the solar cell, the fluorescent nanomaterials convert long-wavelength light into visible light, increasing the energy spectrum absorption range, thereby reducing optical loss and improving optical utilization.
[0070] While specific embodiments of the invention have been described in detail by way of examples, those skilled in the art should understand that the examples are for illustrative purposes only and not intended to limit the scope of the invention. Those skilled in the art should understand that modifications can be made to the above embodiments without departing from the scope and spirit of the invention. The scope of the invention is defined by the appended claims.
Claims
1. A solar cell, characterized in that, The invention includes a fluorescent nano-passivation antireflection film, comprising: 0.1-0.3g polyvinyl chloride, 0.4-0.6g o-nitrophenyl octyl ether, 0.15-0.25g aminated silica microspheres, and 0.05-0.15g fluorescent nanopowder; the fluorescent nanopowder is an anti-Stokes fluorescent nanopowder, and the material is NaYF4:Ln. 3+ , It also includes a silicon substrate, an emitter, a first passivation layer, a second passivation layer, and a first electrode that penetrates the emitter, the first passivation layer, and the second passivation layer and forms an electrical connection with the silicon substrate, all located on the first surface of the silicon substrate in a direction away from the silicon substrate; the second passivation layer is the fluorescent nano-passivation antireflection film; and a tunneling oxide layer, a phosphorus-doped polycrystalline silicon layer, a third passivation layer, and a second electrode are also sequentially disposed on the second surface of the silicon substrate in a direction away from the silicon substrate.
2. The solar cell according to claim 1, characterized in that, The preparation method of the fluorescent nano-passivated antireflective film includes the following steps: Mix 0.1-0.3g of polyvinyl chloride, 0.4-0.6g of o-nitrophenyl octyl ether, 0.15-0.25g of aminated silica microspheres and 0.05-0.15g of fluorescent nanoparticles, and add 1-5 mL of tetrahydrofuran to obtain a mixture; The mixture was homogenized in an ultrasonic apparatus to obtain a suspension; A passivation and antireflection film is deposited on the surface of a solar cell using a suspension coating method.
3. The solar cell according to claim 2, characterized in that, The preparation process of the anti-Stokes fluorescent nanopowder is as follows: a complexing agent and sodium fluoride are added to a lanthanum salt solution to obtain a mixed solution, wherein the concentration of the lanthanum salt solution in the mixed solution is 0.1-2 mol / L, the concentration of the complexing agent is 0.1-2 mol / L, and the concentration of the sodium fluoride is 0.1-1 mol / L.
4. The solar cell according to claim 3, characterized in that, The lanthanum salt solution is yttrium oxide dissolved in dilute acid, and ytterbium oxide, thulium oxide or erbium oxide dissolved in dilute acid.
5. The solar cell according to claim 4, characterized in that, The dilute acid is dilute nitric acid or dilute hydrochloric acid.
6. The solar cell according to claim 3, characterized in that, The complexing agent is trisodium citrate or disodium ethylenediaminetetraacetate.
7. The solar cell according to claim 1, characterized in that, The preparation process of the aminated silica microspheres is as follows: Slowly add 2-6 mL of ammonia and 2-6 mL of tetraethyl orthosilicate to 50-100 mL of ethanol and 5-30 mL of distilled water, stir at 20-40°C for 16-32 hours, collect the fixed product, and obtain silicon dioxide. After sonicating 1-4 g of silica and 20-80 mL of toluene for 10-30 minutes, 2-6 mL of 3-aminopropyltriethoxysilane was slowly added dropwise. Under nitrogen protection, the mixture was stirred at 100-150 °C for 10-16 hours. The solid was separated, washed with ethanol and acetone, and then vacuum dried at 40-80 °C for 16-32 hours to obtain aminated silica microspheres.
8. A photovoltaic module, characterized in that, It includes, from top to bottom, a glass layer, a first encapsulant layer, a solar cell, a second encapsulant layer, and a backsheet, wherein the solar cell is any one of claims 1-7.
Citation Information
Patent Citations
Crystalline silicon solar battery with upper / lower conversion luminescent structure and manufacturing method for crystalline silicon solar battery
CN102364691A
Wavelength conversion film, solar battery module using the same, method for producing the wavelength conversion film, and method for manufacturing the solar battery module
WO2010001703A1
